2017
DOI: 10.12688/wellcomeopenres.11466.2
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol: A multi-centre, double blind, randomised, placebo-controlled, parallel group, phase II trial (RIDD) to determine the efficacy of intra-nodular injection of anti-TNF to control disease progression in early Dupuytren’s disease, with an embedded dose response study.

Abstract: Dupuytren’s disease is a common fibrotic condition of the hand affecting 4% of the population and causes the fingers to curl irreversibly into the palm. It has a strong familial tendency, there is no approved treatment for early stage disease, and patients with established digital contractures are most commonly treated by surgery. This is associated with prolonged recovery, and less invasive techniques have high recurrence rates. The myofibroblasts, the cells responsible for the excessive matrix deposition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…This phase 2a randomised trial shows that a single intranodular injection of 40 mg adalimumab in 0.4 ml in patients with Dupuytren's disease is safe and leads to down regulation of the myofibroblast phenotype as evidenced by reduced expression of α-SMA and type I procollagen proteins. Having defined the most efficacious dose and preparation and based on these positive proof of concept data we are now proceeding with a phase 2b trial in 138 patients with early stage Dupuytren's disease randomised 1:1 to receive 4 injections of adalimumab or placebo at 3 month intervals and followed for a total of 18 months from baseline [ 21 ]. Our study also illustrates the utility of using early stage fibrotic human tissue to elucidate novel therapeutic targets [ 18 ] that can be translated to the clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phase 2a randomised trial shows that a single intranodular injection of 40 mg adalimumab in 0.4 ml in patients with Dupuytren's disease is safe and leads to down regulation of the myofibroblast phenotype as evidenced by reduced expression of α-SMA and type I procollagen proteins. Having defined the most efficacious dose and preparation and based on these positive proof of concept data we are now proceeding with a phase 2b trial in 138 patients with early stage Dupuytren's disease randomised 1:1 to receive 4 injections of adalimumab or placebo at 3 month intervals and followed for a total of 18 months from baseline [ 21 ]. Our study also illustrates the utility of using early stage fibrotic human tissue to elucidate novel therapeutic targets [ 18 ] that can be translated to the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Repurposing anti-TNF for Dupuytren's disease (RIDD) is a two-part phase 2 randomised, double-blinded placebo-controlled dose response study to assess the efficacy of local injection of adalimumab in patients with DD. The protocol was reviewed by the South Central Oxford B Research Ethics Committee (Reference number 15/SC/0259) and the Medicine and Healthcare products Regulatory Authority (EudraCT no: 2015-001780-40) and has been published [ 21 ] (details of subsequent amendments in appendix). The phase 2a dose escalation study reported here was performed at a single centre in the UK at the Edinburgh Department of Plastic Surgery at St John's Hospital, NHS Lothian.…”
Section: Methodsmentioning
confidence: 99%
“… 4 Additionally, because DD is associated with other forms of fibrosis, it may serve as an ideal human model system for fibrotic disease, and the routine excision of tissue as a part of treatment facilitates experimental medicine studies. 5 …”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies have shown the inhibitory effects of TNFi in Dupuytren's contracture by inhibiting myofibroblast activity and the contractile apparatus [ 17 ]. A phase II clinical trial will assess the role of intralesional adalimumab in early Dupuytren's contracture [ 18 ]. Thus, TNFi could possibly help address both the musculoskeletal and dermatological manifestations.…”
Section: Discussionmentioning
confidence: 99%